صورة المملكة العربية السعودية في أدب الرحلات الماليزي: مطار الملك عبد العزيز الدولي أنموذجًا (Depiction of Saudi Arabia in the Malaysian Travel Literature: A Study on King Abdul Aziz International Airport ) - إبراهيم, مجدي حاج; بنت محمد علي سيف الدين, رابعة العدوية (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
حظي الأدب الماليزي الحديث بأعمال في أدب الرحلات صور فيها أصحابها رحلاتهم، ودونوا ما جرى لهم من أحداث ومواقف. تتناول هذه الدراسة كتابين من أدب الرحلات الماليزي؛ هما: "خطوات عبر الزمن" لأرينا واتي، و"رحلة في طلب الحكمة" لعبد الله حسين. وتكشف الدراسة أن كلا الأديبين قدم تقريرا مفصلا ودقيقا عن رحلته الخاصة لأداء مناسك الحج، وعلى الرغم من أن الفارق الزمني بين الرحلتين قصير جدا لا يتجاوز عشر سنوات، فقد سجل كلا الأديبين انطباعا مختلفا عن الآخر تجاه المعاملة التي تلقاها على أرض الحرمين الشريفين لا سيما في مطار الملك عبد العزيز الدولي. ويؤكد الأديبان الماليزيان على ضرورة العمل نحو تحسين الأداء والعمل الإداري والفني والتقني والإجراءات والتدابير الأمنية في المطار، إذ لا بد للمطار أن يكون واجهة حضاريّة تعطي الانطباع الحقيقي عن المستوى الحضاري والحراك التنموي الذي تعيشه البلاد، فهو أول ما ينطبع في أذهان المسافرين القادمين، وآخر ما يترسخ في أذهان المسافرين المغادرين. الكلمات المفتاحية: أدب الرحلات الماليزي، أرينا واتي، عبد الله حسين، المملكة العربية السعودية، مطار الملك عبد العزيز الدولي. Abstract Travel literary works can be found in modern Malay literature in which authors substantially depict their journeys and record events and situations that they see and experience. This paper studies on two books of Malaysian travel literature: "Meniti Kala" by Arena Wati, and "Perjalanan Mencari Hikmah" by Abdullah Hussain. This study found that both authors provided detailed and precise narrative of their journeys while performing Hajj. Although the time difference between those two trips was lesser than ten years, each author had different impressions on the treatment they received on the Holy Land especially at King Abdul Aziz International Airport. It is obvious in their writings that they are on the same page as they emphasise the needs to work on improving performances, administrative and technical works, security procedures and measures at the airport as airport is the hallmark of a country that gives real impression on civilizational level and developmental mobilization that has been experienced by the country. It is the first thing that stamped on incoming travellers’ minds and the last thing that would solidify their impression when they depart. Keywords: Malaysian Travel Literature, Arena Wati, Abdullah Hussain, Saudi Arabia, King Abdul Aziz International Airport.